2013
DOI: 10.1038/nsmb.2699
|View full text |Cite
|
Sign up to set email alerts
|

Rbfox proteins regulate alternative mRNA splicing through evolutionarily conserved RNA bridges

Abstract: Alternative splicing (AS) enables programmed diversity of gene expression across tissues and development. We show here that binding in distal intronic regions (>500 nucleotides (nt) from any exon) by Rbfox splicing factors important in development is extensive and is an active mode of splicing regulation. Similarly to exon-proximal sites, distal sites contain evolutionarily conserved GCATG sequences and are associated with AS activation and repression upon modulation of Rbfox abundance in human and mouse exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
346
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(387 citation statements)
references
References 70 publications
20
346
1
Order By: Relevance
“…Alternatively, this may be related to the observed Nova1 up-regulation upon Nova2 silencing, revealing a compensatory mechanism that could decrease physiological perturbations due to changes in splicing pathways. Reciprocal compensatory regulation between RBP paralogs has been previously observed in the Nova and other RBP families (49,50).…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellsmentioning
confidence: 94%
“…Alternatively, this may be related to the observed Nova1 up-regulation upon Nova2 silencing, revealing a compensatory mechanism that could decrease physiological perturbations due to changes in splicing pathways. Reciprocal compensatory regulation between RBP paralogs has been previously observed in the Nova and other RBP families (49,50).…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellsmentioning
confidence: 94%
“…3B). Interestingly, a subset of enhanced exons also contained UGCAUG motifs proximal to the downstream constitutive 39 splice site, perhaps implicating distant motifs in Rbfox2-dependent exon inclusion (Lim and Sharp 1998;Lovci et al 2013). Most of the motif occurrences near regulated exons were well conserved.…”
Section: Rbfox2 Rna Map Reveals Position-dependent Regulation Of Cassmentioning
confidence: 99%
“…Statistically significant genic clusters of FHFOX2 binding were determined next using cross-link sites extended on either side by 12 nt as input into the CLIPper algorithm (available at https://github.com/YeoLab/clipper) (Lovci et al 2013). Allowing for the calling of clusters within pre-mRNA regions, we identified 40,243 FHFOX2 clusters and only 2961 UntagFOX2 clusters (gene-level false discovery rate [FDR] # 0.05; P # 0.05).…”
Section: Rbfox2 Individual Nucleotide-resolution Clip (Iclip) Is Enrimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on RSSs in eukaryotic genes revealed widespread occurrence of long-range RRI with diverse functions such as riboswitches (Li and Breaker 2013) and mediators of exon skipping (Lovci et al 2013), mutually exclusive exon choice (Kreahling and Graveley 2005;Yang et al 2011), and other types of alternative splicing events (Raker et al 2009;Pervouchine et al 2012). Many of these structures are located in regions lacking reliable sequence alignments and contain long, ultraconserved stretches of complementary nucleotides, in which the interacting bases can be separated by distances as large as 10 kb.…”
Section: Introductionmentioning
confidence: 99%